Railroads and Micro-regional Growth in Prussia - Erik Hornung (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
We study the effect of railroad access on urban population growth. Using GIS techniques,we match triennial population data for roughly 1000 cities in nineteenth-century Prussiato georeferenced maps of the German railroad network. We find positive short- andlong-term effects of having a station on urban growth for different periods during18401871. Causal effects of (potentially endogenous) railroad access on city growthare identified using instrumental variable and fixed-effects estimation techniques. Ourinstrument identifies exogenous variation in railroad access by constructing straight-linecorridors between terminal stations. Counterfactual models using pre-railroad growthyield no evidence in support of the hypothesis that railroads appeared as a consequenceof a previous growth spurt.
Keywords: O18; O33; N73; 330; Railroads; technological diffusion; economic growth; population growth; Schienenverkehr; Verkehrserschließung; Stadtwachstum; Innovationsdiffusion; Preußen